2017
DOI: 10.1128/jvi.02511-16
|View full text |Cite
|
Sign up to set email alerts
|

Structural Definition of Duck Major Histocompatibility Complex Class I Molecules That Might Explain Efficient Cytotoxic T Lymphocyte Immunity to Influenza A Virus

Abstract: A single dominantly expressed allele of major histocompatibility complex class I (MHC I) may be responsible for the duck's high tolerance to highly pathogenic influenza A virus (HP-IAV) compared to the chicken's lower tolerance. In this study, the crystal structures of duck MHC I (Anpl-UAA*01) and duck β2-microglobulin (β2m) with two peptides from the H5N1 strains were determined. Two remarkable features were found to distinguish the Anpl-UAA*01 complex from other known MHC I structures. A disulfide bond forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 74 publications
(94 reference statements)
3
39
0
Order By: Relevance
“…1D). Many of these residues, namely, Y7, Y58, T140, K143, W144, Y158, and Y170, can interact directly by hydrogen bonds or indirectly by participating in hydrogen bond networks with the peptide ligand, which has been extensively reported for other pMHC-I structures (33,36,(42)(43)(44) and is discussed for pXela-UAAg below.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…1D). Many of these residues, namely, Y7, Y58, T140, K143, W144, Y158, and Y170, can interact directly by hydrogen bonds or indirectly by participating in hydrogen bond networks with the peptide ligand, which has been extensively reported for other pMHC-I structures (33,36,(42)(43)(44) and is discussed for pXela-UAAg below.…”
Section: Resultsmentioning
confidence: 89%
“…In addition, because the AB loop and CD loop in the pXela-UAAg a1 domain and the EF loop in the a2 domain have their own features, the AB loop in pXela-UAAg can directly combine with Xela-b2m; the EF loop and CD loop are shorter than those in mammals, causing the CD loop to contain two fewer amino acids and the EF loop to contain one fewer amino acid in nonmammalian structures than in mammalian structures. However, pXela-UAAg is similar to known nonmammalian structures (chickens, ducks, and grass carp) (3,5,36,43). Moreover, four amino acids in Xela-b2m that interact with Xela-UAAg are conserved in mammals and other vertebrates.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This limited repertoire may explain why chickens show more severe clinical outcomes due to HPAI such as H5N1 compared to waterfowl, as ducks show extensive diversity in their MHC class I alleles which allows the immune system greater coverage for viral variation ( 165 ). A recent investigation into duck MHC class I molecules found that the duck Anpl -UAA*01 complex showed similar peptide binding properties to HLA-A*02:01 in humans and as such appears to cover a greater array of influenza A virus epitopes compared to similar chicken MHC molecules such as BF2*2101 ( 166 ). Furthermore, migratory shorebirds which act as reservoirs for AI viruses (in particular LPAI H9N2) show increased diversity in their MHC alleles, likely as a mechanism for protecting against foreign pathogens that may be encountered during migration.…”
Section: Host Susceptibility Factorsmentioning
confidence: 99%